E-LEARNING MENGGUNAKAN MOODLE BERBASIS WEB DI SMP MA’HAD ISLAM SEMARANG (Information Technology and Telematics, 2013)
Abstract The teaching methode used in Ma’had Islam Junior High School is still using the manual way. It’s not in testing to the student. This is the caused of based of the student to understanding the material of the  lesson.As we know, that the information teknology is develop fastly, it make the teaching learning activity can be maximalied with using it. The goal of the research is to build E-Learning application with using Moodle  based on Web in Ma’had Islam Junior High School Semarang.E-Learning system is made by using Moodle and the language of PHP programme and data base (My Sql). The E-Learning system is planned by using assist instrument of system planning.With the research we conclude that the system made and implementasied with so many facilities. That are the administrator, teacher, and student, lessons managing, input of assignment, exercise, and examination.All of the components make the teacher easy to give the lesson, and the student easy to get information about of the lesson.Keyword: E-Learning , Moodle, PHP, MySQL,Teaching Learning activity